Effects of sodium diethyldithiocarbamate on ischemia-reperfusion-induced brain injury in Mongolian gerbil - Chen Dong-ming; Li Wan-hai; Xu Bing-xiang; Tao Xue-bin; Chen Jie (Acta Pharmacologica Sinica, 2016)
Brain injury in Mongolian gerbil (Merisones unguiculatus) was induced by occluding bilateral common carotid arteries for 60 min followed by reperfusion for 5 or 30 min. Oxygen free radicals in brain tissue were measured by electron spin resonance (ESR) technique, malondialdehyde (MDA) was measured by fluorescence spectrometry, and superoxide dismutase (SOD) was measured by nitrite kit. Oxygen free radicals and MDA were not significantly increased, but activities of T-SOD and Mn-SOD were decreased after 60 min of cerebral ischemia. The free radicals were increased at 5-min reperfusion, and then reduced to the level of ischemia group after 30-min reperfusion. MDA was increased remarkably after reperfusion of 30 min, whereas the activity of SOD continued to decrease. Sodium diethyldithiocarbamate (DTC), i.v. 5-100 mg.kg-1 15 min before occlusion, decreased the production of MDA and increased the activities of T-SOD and Mn-SOD. The formation of oxygen free radicals was depressed by i.v. DTC 50 mg.kg-1. The result suggested that the protective effects of DTC on ischemia-reperfusion-induced brain injury might be induced by scavenging the oxygen free radicals, increasing the Mn-SOD activity and decreasing the production of MDA.